HUBUNGAN KEPADATAN JENTIK DENGAN PENYAKIT DBD DI KELURAHAN SENDANGMULYO KOTA SEMARANG MELALUI PENDEKATAN ANALISIS SPASIAL - Saraswati, Lintang Dian; Martini, Martini (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2012)
ABSTRACT The highest incidence of dengue in Semarang City is in Sendangmulyo Village. One risk factor for DHF is a high vector density. To support the success of efforts to eradicate the vector, dengue entomology surveys is a must by using House Index (HI), Container Index (CI), and Breteau Index (BI). The purpose of this study was to determine the relationship larvae density with the incidence of dengue in the Sendangmulyo Village through a spatial approach. This type of research is a descriptive survey research using a study design with the ecological approach to spatial correlation. The research sample consists of 435 homes drawn using systematic random sampling techniques, and purposive sampling. The survey carried out by visual larvae. Point coordinates found DHF cases as many as 327 cases. Statistical analysis was performed with the Pearson-Product Moment correlation and analysis of spatially Weighted Regression with GeoDa. The results showed that the HI value of 33.79%, CI of 15.77%, and BI of 57.93%. In addition, dengue cases were equally distributed in the region Sendangmulyo Village. Statistical test showed that there was no significant relationship between the HI, CI, BI and DHF cases. From this study, it can be concluded that this index of larvae do not have a meaningful relationship with the incidence of dengue in the Sendangmulyo Village. Key words: density of larvae, DBD, spatial Kesmasindo. Volume 5( 1) Januari 2012, hlm.   52-64